2016
DOI: 10.1177/0956797616661182
|View full text |Cite
|
Sign up to set email alerts
|

Young Children See a Single Action and Infer a Social Norm

Abstract: Human social life depends heavily on social norms that prescribe and proscribe specific actions. Typically, young children learn social norms from adult instruction. In the work reported here, we showed that this is not the whole story: Three-year-old children are promiscuous normativists. In other words, they spontaneously inferred the presence of social norms even when an adult had done nothing to indicate such a norm in either language or behavior. And children of this age even went so far as to enforce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(95 citation statements)
references
References 40 publications
3
90
0
2
Order By: Relevance
“…labeling, "this is daxing") or teaching behaviors (e.g. addressing the children) to indicate the presence of a rule (Schmidt, Butler, Heinz, & Tomasello, 2016).…”
Section: Can Change Rulesmentioning
confidence: 99%
“…labeling, "this is daxing") or teaching behaviors (e.g. addressing the children) to indicate the presence of a rule (Schmidt, Butler, Heinz, & Tomasello, 2016).…”
Section: Can Change Rulesmentioning
confidence: 99%
“…These cognitive abilities are supported by a psychological system that has evolved to understand the minds of others and to navigate complex social group behavior (49)(50)(51). Well-documented cognitive biases reinforce cultural transmission, including preferences for similar others (homophily) (52) and proclivities for conformity (53), consensus (54)(55)(56), prestige (57,58), and social norms (59)(60)(61)(62).…”
mentioning
confidence: 99%
“…Moreover, they argue that young children are biased to expect information that is intentionally communicated to them to be relevant, important, and generalizable. Indeed, a number of empirical studies have shown that even infants process information differently and form difference expectations when evidence is deliberately manifested for them (Futó et al, 2010;Egyed, Király, & Gergely, 2013;Yoon, Johnson, & Csibra, 2008;) and by early childhood they treat that information as more important and generalizable in a variety of ways (Bonawitz et al, 2011;Butler & Markman, 2012, 2016Butler et al, 2015;Schmidt et al, 2016;Vredenburgh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Seeing novel properties or actions demonstrated intentionally, with cues suggesting the pedagogical intent to transmit important infomation, leads children to make inductive generalizations about that evidence that are stronger and more resistant to counter-evidence (Butler & Markman, 2012b, 2016 Hernik & Cisbra, 2015), leads them to construct radically different conceptions of novel categories (Butler & Markman, 2014;Futó, Téglás, Csibra, & Gergely, 2010;Kovács, Téglás, Gergely, & Csibra, 2016;Yoon, Johnson, & Csibra, 2008), and leads them to infer that Pedagogy and counterevidence 6 the demonstrated action is the only (Bonawitz, Shafto et al, 2011) or normatively correct (Schmidt, Butler, Heinz, & Tomasello, 2016; Vrendenburgh, Kushnir, & Casasola, 2014) way to act. Taken together, this evidence suggests that children's sensitivity to whether or not actions are carried out with pedagogical intent towards the child shapes the inferences children make about the evidence those actions produce.…”
Section: Children's Use Of Social Cues To Guide Inductive Inferencesmentioning
confidence: 99%